Self-esteem and state-trait anxiety in Lima's university adults - Alejandra Rodrich Zegarra (Interacciones)
Background: This study sought to determine the relationship between self-esteem and anxiety in emerging adults from private universities in Lima. Method: Cross-sectional and correlational in design, it was aimed at determining the degree or strength of association between self-esteem, state/trait anxiety in emerging adulthood, for this purpose, the Coopersmith Self-Esteem Inventory (Form C) and the Anxiety Questionnaire State-Trait (IDARE) were applied to 221 university students of both sexes, aged between 18 to 25 years. Results: In the hypothesis test, a statistically significant negative correlation coefficient was obtained between self-esteem and state/trait anxiety, being the size of the median effect in both cases. Regarding comparisons in self-esteem and anxiety trait/state according to sex and age, no differences were found. Conclusion: From the analyzes, it is concluded that there are an inverse and significant relationship between self-esteem and state/trait anxiety in emerging adults from Lima.